Design of Integrated Gasifier and Steam Methane Reformer - Ghouse, Jaffer H. (My University, 2016)
While the quest of the human civilization continues towards a more sustainable energy resource, current energy conversion technologies need to be improved such that the rate of environmental impact that has occurred due to the rapid industrialization since the 20th century is mitigated. This search has motivated research into new energy conversion technologies that aim to reduce the environmental impact by either improving the efficiencies of existing technologies, developing new technologies with zero emissions or by improving reliability and reducing the cost of renewable energy. Process intensification through process integration is one of the areas of active research that improves the system efficiency by exploiting the synergies that exist between different processes. This thesis considers the design and operational feasibility of heat integrating two conventional industrial processes – gasification and steam reforming of methane for application in polygeneration. To this end, complex mathematical models that describe the integrated system are developed to study different design prospects and to determine if the device can be safely operated in a plant producing electricity, liquid fuels and hydrogen. The designs proposed in this thesis show that significant methane conversion comparable to industrial reformers can be achieved while providing the required cooling duty to the gasifier. The proposed integrated system produces hydrogen rich reformer synthesis gas (hydrogen and carbon monoxide) that can be blended with the hydrogen lean coal synthesis gas providing flexibility to change the molar H2/CO ratio necessary for different downstream processes in a polygeneration plant. Moreover, the results show that the integration helps improve plant carbon efficiency and reduce CO2 emissions. The major contribution of this thesis is the development of designs based on representative mathematical models that are safe to operate for producing several chemicals in polygeneration plants.
Keywords: Polygeneration; Process Intensification; Gasifier; Steam Methane Reforming; Integrated